Study of obstacles of fish culture in Khartoum State (Omdurman, Khartoum and Khartoum north, case study) - Hassan, M. Yagoub; Amal, A. Alsiddig; Fatima, I. Omer; Maimouna, A. Hassan (International Journal of Aquaculture Research and Development, 2023)
The present study aimed to provide baseline information of fish culture status (obstacles) of Omdurman, Khartoum and Khartoum north in the Khartoum state in Sudan due to there is little or lack of information in this field. 30 owners of farm were questioned from Omdurman, Khartoum and Khartoum north, 10 farms for each location; Descriptive analysis was done for analyzing the raw data of the study by using Excel Microsoft Software 2007. Social data showed that male farm owners group was dominant in third sites 100%. Age groups of fishermen ranged between 20 to 60 years; where age group 31- 40 Khartoum north, age group 41- 50 was dominant in O mdurman and age group 51-60 year was dominant in Khartoum. Six educational categories were recorded where University education was dominant in the three locations 50%, 50% and 70% respectively; whereas, postgraduate was the second in the tow location: O mdurman and Khartoum 20% and the secondary education were the third in Khartoum 30%. all farm owners were married 100% in three sites; As regards to the farm owners other activities results showed that most of them were practicing other activities (farmers, business owner, officers and workers). Category of farmer was dominant 90% secondly business owner and officer 70% and 50% respectively. Data showed that the problems (Varanus niloticus, birds, marketing, fees and thefts) was dominant in three locations had the highest percentage 90%, 80%, 60%, 30% and 10% respectively. and according to production cost in three locations arranged: (feeds, workers, fingerlings, water and technical supervision) 50, and 70% and 40%, 50% and 70% and 30%, 40% and 50% and 10, 20 and 40% and 10, 20 and 30% respectively. Category of feeds dominant followed by workers and fingerlings, the best Method to obtain of information, the results showed that Bulletins was dominant in three sites 80%, 30% and 90%; whereas, field visits in three location was the second 60%, 90% and 0%, Radio programs in three location was the third 60%, 10% and 60% and the lowest percentage; Seminars and television 40%, 50% and 40%, and 30%, 0% and 0%. For the best location to obtain information results revealed that the General Director of Fisheries Ministry of Agriculture, Animal Resources and Irrigation - Khartoum State was dominant in the three locations 90%, 80% and 90%, whereas, Universities in three location was the second 40%, 20% and 0%, and the lowest percentage Central Research of fisheries 40%, 0% and 0%, and Internet 10%, 20% and30%. Also result showed most of the farm owners in three sites all them need to training courses in deferent programmers (Fish extinction, Fish feeding, Fish production and Fish marketing) according to this percentages 60%, 30% and 50%, and 30%, 10% and 50%, and 10%, 10% and 30%, and 10%, 0% and 20% respectively.
Keywords: fish farms; problems; Khartoum State and Sudan